Transformation of Streptomyces granaticolor with natural and recombinant plasmid vectors - Petrícek, M; Smrcková, I; Tichý, P (Folia microbiologica, 1985)
Protoplasts of Streptomyces granaticolor were found to be transformable by the broad-host-range plasmid pIJ350 but no transformants were detected when the narrow-host-range plasmid pIJ2 or the shuttle vector pPM66 (pIJ350--pBR322) isolated from E. coli cells were used. The onset of blue colour granaticin production by S. granaticolor cells was used as a marker to prepare protoplasts with a high transformation capacity. The presence of a restriction system is discussed.
Keywords: spory bakteriální; Recombination, Genetic; restrikční enzymy; rekombinace genetická; Plasmids; bakteriální transformace; DNA Restriction Enzymes; Streptomyces; Transformation, Bacterial; plazmidy; Spores, Bacterial